Mahamane Diallo - Bouwéré village, Mali - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Mahamane Diallo is a cattle farmer from the village Bouwéré in Mali. In the video he talks about how the villagers have had to change the way they feed the cattle because of the reduced space to graze due to the scarcity of water. Instead of feeding of grass the cattle is now allowed to feed on their crop fields after the harvest as well as being herded in other countries. As a way to cope with the loss in cattle, the villagers have started using the waterholes as fishponds to create additional income.